Florid xanthogranulomatous cholecystitis masquerading as invasive gallbladder cancer leading to extensive surgical resection - Rastogi Archana; Singh Deepak; Sakhuja Puja; Gondal Ranjana (Indian Journal of Pathology and Microbiology, 2010)
Xanthogranulomatous inflammation of gallbladder wall can extend and infiltrate adjacent organs which can be mistaken for malignancy on preoperative investigations and, intraoperatively, often leads to extensive surgical resections. Only the histopathologic examination of the specimen allows correct diagnosis. We hereby review clinicopathologic findings of six cases which underwent extensive surgeries on clinical, radiological and intraoperative suspicion of gallbladder carcinoma which turned out to be xanthogranulomatous cholecystitis (XGC). There was no evidence of malignancy on histopathologic examination. Xanthogranulomatous inflammation extended into liver, duodenum, colon and stomach in case 1; liver and colon in case 2; liver, duodenum, colon in case 3; stomach, duodenum, colon in case 4; stomach and duodenum in case 5 and duodenum and colon in case 6. Lymph nodes in all the six cases showed reactive hyperplasia. We present here the clinico-radiologic findings of these cases, techniques which may help differentiate between an XGC and a gallbladder carcinoma and also discuss the management of these cases.